Spontaneous healing of the tympanic membrane after traumatic perforation in rats - Araújo,Marcos Miranda de (2014)
OBJECTIVE: The objective of the present study was to assess the healing of traumatic tympanic membrane perforation in rats. METHODS: The tympanic membrane from male Wistar rats was perforated in the anterior and posterior portions to the handle of the malleus. Five tympanic membranes were evaluated 3 days after tympanic perforation; 5 after 5 days; 5 after 7 days; 3 after 10 days; and 4 after 14 days. The tympanic membranes were submitted to histopathological evaluation after hematoxylin-eosin staining. RESULTS: Tympanic membrane closure occurred at about 7-10 days after injury and the healing process was complete by day 14. The proliferative activity of the outer epithelial layer was present close to the handle of the malleus and to the tympanic annulus. CONCLUSION: The spontaneous healing process of the tympanic membrane starts from the outer epithelial layer, with later healing of the lamina propria and the mucosal layer.